2003
DOI: 10.1088/0031-9155/48/2/307
|View full text |Cite
|
Sign up to set email alerts
|

Methods for measuring the infrared spectra of biological cells

Abstract: Infrared (IR) spectroscopy of biological cells is a growing area of research, with many papers focusing on differences between the spectra of cancerous and noncancerous cells. Much of this research has been performed using a monolayer of dehydrated cells. We posit that the use of monolayers can introduce artefacts that lead to an apparent but inaccurate measurement of differences between cancerous and noncancerous cells. Additionally, the use of dried cells complicates the extraction of biochemical information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
73
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 28 publications
2
73
0
Order By: Relevance
“…22 Fourier transform infrared spectroscopy (FTIR) can also be used in spectroscopic discrimination and imaging of biological cells and tissues. [23][24][25][26][27][28][29] We have also developed a proteomics method for early detection and diagnosis of oral malignancy based on protein profiles of serum, saliva, and tissue homogenate samples using high performance liquid chromatography coupled to laser-induced fluorescence (HPLC-LIF) detection. 30 The work has shown that a large number of new proteins are present in serum and tissue samples in malignancy, supporting our Raman spectra results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Fourier transform infrared spectroscopy (FTIR) can also be used in spectroscopic discrimination and imaging of biological cells and tissues. [23][24][25][26][27][28][29] We have also developed a proteomics method for early detection and diagnosis of oral malignancy based on protein profiles of serum, saliva, and tissue homogenate samples using high performance liquid chromatography coupled to laser-induced fluorescence (HPLC-LIF) detection. 30 The work has shown that a large number of new proteins are present in serum and tissue samples in malignancy, supporting our Raman spectra results.…”
Section: Introductionmentioning
confidence: 99%
“…30 The work has shown that a large number of new proteins are present in serum and tissue samples in malignancy, supporting our Raman spectra results. [22][23][24] Raman spectroscopy has several advantages over fluorescence and FTIR spectroscopy. Unlike fluorescence, Raman spectrum can be produced by excitation at any wavelength and it is possible to obtain more detailed information on the biochemical contents of the samples.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Raman and infrared vibrational spectroscopic techniques have also been exploited for investigating eukaryotic and prokaryotic cells. [11][12][13][14][15] As can be seen from the literature, among these two methods, infrared, probably due to its higher sensitivity, has been most widely used. Several successful Fourier transform infrared (FTIR) studies for discrimination of Pap smear and other exfoliated cells have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, samples need still to be dried and FTIR spectroscopy is also prone to other sampling errors like uneven thickness. 15 Raman microspectroscopy, on the other hand, is less sensitive but has confocal properties, is not perturbed by water, and offers higher spatial resolution, down to about the micron level, making it an adapted tool for single-cell analysis. In the present investigation, both FTIR and micro-Raman approaches have been compared for characterizing cell types and phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…14 Particularly, two vibrational spectroscopic techniques namely FTIR and Raman spectroscopies are commonly used as complementary analytical tools for in situ and in vivo measurements of samples of biological origin. [15][16][17][18][19][20] This is mainly due to their unique capability of providing labelfree intrinsic chemical and structural information of living biological samples at tissue, cellular, or sub-cellular resolutions. 21 In addition, Raman spectroscopy is well-suited for studying the structure of lipids because this technique is noninvasive, nondestructive, and involves no labeling as well as minimal sample preparation.…”
Section: Introductionmentioning
confidence: 99%